(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
Using online documentary analysis, this paper examined the ability of a public higher education in Ghana to adapt to change in relation to teaching and learning in the midst of COVID-19 pandemic. Measures taken to ensure uninterrupted migration to online teaching and learning included a regular monthly supply of data bundle from an internet service provider to faculty members, select senior staff and students as well as regular training in the use of the SAKAI Learning Management System. Challenges encountered by students and faculty members include inadequate internet access when supplementary virtual modes were added to SAKAI to enhance the institution’s teaching programs. Despite these challenges, the University of Ghana was able to complete the 2019/2020 academic year.